Effect of Steeping Green Tea (Camellia Sinensis L.) Against IL6 and IL 10 Levels in Rats Exposed to Cigarette Smoke - Surya Ayu Pratiwi; Hadi Sarosa; Setyo Trisnadi (Asian Journal of Social and Humanities, 2023)
The prevalence of smokers in Indonesia is more than 25% of the total population. Cigarette smoke contains numerous free radicals that trigger the formation and increase of Reactive Oxygen Species (ROS) within the body, leading to inflammation and cytokine production. Green tea contains catechins known for their potent antioxidant properties. This study aims to assess the levels of Interleukin 6 and Interleukin 10 in rats exposed to cigarette smoke. The research method used was the post-test only control group design, involving 24 male Wistar rats divided into 4 groups: Normal group (N), Control - (Cigarette Smoke), Control + (Cigarette Smoke + 1.44 mg/day Vitamin E), P. (Cigarette Smoke + 3.6 ml Green Tea Infusion). Interleukin 6 and Interleukin 10 levels were measured after 14 days of treatment. Data were analyzed using One Way Anova. The mean IL-6 level in the Control (-) group was the highest (141.75±6.24 pg/ml), while the Sham group had the lowest (73.58 ± 4.57 pg/ml) IL-6 level. One Way Anova results showed a p-value of <0.001 for both IL-6 and IL-10 levels, indicating a significant difference among the four groups. Post Hoc LSD test results indicated that the IL-6 levels in the K(+) group were relatively similar to the IL-6 levels in the P group (p=0.172). Post Hoc LSD test results for IL-10 levels between the two groups were all significant, with a p-value of <0.001. The administration of green tea infusion was shown to affect the Interleukin 6 levels, while green tea infusion did not have a significant impact on Interleukin 10 levels in white rats exposed to cigarette smoke.